Reversed Senescence of Retinal Pigment Epithelial Cell by Coculture With Embryonic Stem Cell via the TGFβ and PI3K Pathways - Wang, Shoubi; Liu, Yurun; Liu, Ying; Li, Chaoyang; Wan, Qi; Yang, Liu; Su, Yaru; Cheng, Yaqi; Liu, Chang; Wang, Xiaoran; Wang, Zhichong (Frontiers in Cell and Developmental Biology, 2020)
Retinal pigment epithelium (RPE) cellular senescence is an important etiology of age-related macular degeneration (AMD). Aging interventions based on the application of stem cells to delay cellular senescence have shown good prospects in the treatment of age-related diseases. This study aimed to investigate the potential of the embryonic stem cells (ESCs) to reverse the senescence of RPE cells and to elucidate its regulatory mechanism. The hydrogen peroxide (H2O2)-mediated premature and natural passage-mediated replicative senescent RPE cells were directly cocultured with ESCs. The results showed that the proliferative capacity of premature and replicative senescent RPE cells was increased, while the positive rate of senescence-associated galactosidase (SA-β-GAL) staining and levels of reactive oxygen species (ROS) and mitochondrial membrane potential (MMP) were decreased. The positive regulatory factors of cellular senescence (p53, p21WAF1/CIP1, p16INK4a) were downregulated, while the negative regulatory factors of cellular senescence (Cyclin A2, Cyclin B1, Cyclin D1) were upregulated. Furthermore, replicative senescent RPE cells entered the S and G2/M phases from the G0/G1 phase. TGFβ (TGFB1, SMAD3, ID1, ID3) and PI3K (PIK3CG, PDK1, PLK1) pathway-related genes were upregulated in premature and replicative senescent RPE cells after ESCs application, respectively. We further treated ESCs-cocultured premature and replicative senescent RPE cells with SB531542 and LY294002 to inhibit the TGFβ and PI3K pathways, respectively, and found that p53, p21WAF1/CIP1 and p16INK4a were upregulated, while Cyclin A2, Cyclin B1, Cyclin D1, TGFβ and PI3K pathway-related genes were downregulated, accompanied by decreased proliferation and cell cycle transition and increased positive rates of SA-β-GAL staining and levels of ROS and MMP. In conclusion, we demonstrated that ESCs can effectively reverse the senescence of premature and replicative senescent RPE cells by a direct coculture way, which may be achieved by upregulating the TGFβ and PI3K pathways, respectively, providing a basis for establishing a new therapeutic option for AMD.